2019
DOI: 10.1016/j.jtcvs.2018.08.116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remote ischemic preconditioning preceding coronary artery bypass grafting on inducing neuroprotection

Abstract: Background: Neurological complications after coronary artery bypass grafting (CABG) reduce quality of life, increase mortality, and inflate resource utilization. The risk of postoperative neurological complications parallels the increasing risk burden of the contemporary patient population. We evaluated the efficacy of remote ischemic preconditioning (RIPC) on inducing neuroprotection.Methods: Seventy patients undergoing first-time CABG were randomly assigned to RIPC or a sham procedure. Structural brain magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 34 publications
0
64
0
Order By: Relevance
“…Patients with normal kidney function at baseline were included except one study that included patients with chronic kidney disease (CKD) who were scheduled for cardiac surgery (17). With regard to the surgery procedures, 20 studies included patients who received on-pump surgeries (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30), while the remaining two studies included patients who received off-pump surgeries (29,31). Proportions of diabetic patients varied among the included studies, and patients with severe cardiac systolic function (left ventricular ejection fraction <30%) were rarely included.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with normal kidney function at baseline were included except one study that included patients with chronic kidney disease (CKD) who were scheduled for cardiac surgery (17). With regard to the surgery procedures, 20 studies included patients who received on-pump surgeries (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30), while the remaining two studies included patients who received off-pump surgeries (29,31). Proportions of diabetic patients varied among the included studies, and patients with severe cardiac systolic function (left ventricular ejection fraction <30%) were rarely included.…”
Section: Search Resultsmentioning
confidence: 99%
“…Uninflated cuffs were used on patients in the control group. Most of the studies used the AKIN definition of AKI, while the RIFLE (13,19,28) and the KDIGO (18,20,30,31) definitions were used in three and four studies, respectively. Table 2 shows the details of study quality evaluation.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup of 1,951 patients from 18 trials underwent cardiac surgery. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The remaining 1,853 patients were included in 14 trials in various surgical settings: organ transplant donors or recipients (five trials), [45][46][47][48][49] tumor resection (five trials), 13,[50][51][52][53] abdominal aortic aneurysm repair (two trials), 54,55 and orthopaedic surgery (two trials) 56,57 (►Table 1). Preconditioning was the preferred study intervention used in 26 trials, 13,[28][29][30][31]33,34,[36][37][38][39][40][41][42][43][44][45][46]…”
Section: Resultsmentioning
confidence: 99%
“…RIPC has been demonstrated to reduce neural damage in experimental models of ischemic stroke, [10][11][12][13] and mitigate ischemic brain damage and neurological sequelae in humans after cardiac surgery. 14 RIPC has recently been applied in the setting of acute stroke, specifically intracranial atherosclerotic stenosis. 15,16 Previous studies showed the safety and feasibility of RIPC with extremely low numbers of side effects in aneurysmal subarachnoid hemorrhage, 17,18 acute ischemic stroke, 19,20 and in patients who undergo mechanical thrombectomy 20 and elective carotid endarterectomy.…”
Section: Introductionmentioning
confidence: 99%